2020
DOI: 10.1021/jacs.0c02633
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Prime Factors to Maximize the Photocatalytic Hydrogen Evolution of Covalent Organic Frameworks

Abstract: Visible light driven hydrogen (H2) production from water is a promising strategy to convert and store solar energy as chemical energy. Covalent organic frameworks (COFs) are front runners among different classes of organic photocatalyst, owing to their tunable porosity, crystallinity, optical and electronic properties.Photocatalytic activity of COFs depends on numerous factors such as band gap, crystallinity, porosity, exciton migration, charge separation and transport, stability etc. However, it is challengin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(184 citation statements)
references
References 72 publications
3
168
0
Order By: Relevance
“…128 Low dihedral angles can be achieved by combining a phenyl ring with heteroatomic rings, that do not possess hydrogen atoms in ortho position to the connecting bond between both rings, such as structures based on boroxine, triazine, bipyridine, pyridine, pyrimidine or tetrazine. 3,129,130 The use of a five membered ring can also enable flat structures such as those based on thiophene. 131 The repulsion of hydrogen atoms on adjacent phenyl rings can also be reduced by introducing a separating alkyne group.…”
Section: Review Articlementioning
confidence: 99%
“…128 Low dihedral angles can be achieved by combining a phenyl ring with heteroatomic rings, that do not possess hydrogen atoms in ortho position to the connecting bond between both rings, such as structures based on boroxine, triazine, bipyridine, pyridine, pyrimidine or tetrazine. 3,129,130 The use of a five membered ring can also enable flat structures such as those based on thiophene. 131 The repulsion of hydrogen atoms on adjacent phenyl rings can also be reduced by introducing a separating alkyne group.…”
Section: Review Articlementioning
confidence: 99%
“…In fact it has been shown that functionalization of a phenyl ring causes similar effects. 207 Another important factor is the rigidity of the building blocks, as more flexible linkers lead to more possible conformations and thus lower crystallinity. 208,209 However, both effects can be countered by the introduction of extra favorable interactions like hydrogen bonding.…”
Section: Linker and Condition Optimizationmentioning
confidence: 99%
“…There is only one exception to the rule that directly relates crystallinity and photochemical HER activity [32]. In this work, Seki, Abe et al systematically analyze the effect of all possible factors on the photocatalytic H2 evolution activity of the β-ketoenamine Tuning the building blocks has also been explored for some COFs, leading to rationally improved activities.…”
Section: Common Synthetic Pathways To Build Efficient and Robust Cofsmentioning
confidence: 99%
“…Due to its appropriate band energy levels, the system with a terphenyl spacer and larger pores, g-C 40 N 3 -COF (Figure 2e, Figure 4c), resulted the most active in the HER. Additionally, β-ketoenamine linked honeycomb-like COFs have been formed by condensation of 1,3,5triformylphloroglucinol (TP) with 4,4 -diamino-p-terphenyl (TPh-NH 2 ) and three derivatives consisting in replacing the central phenyl ring by anthracene (Ant), tetrazine (Tz), or benzothiadiazole (BT), namely TPh-Ant-NH 2 , TPh-Tz-NH 2 , and HTPh-BT-NH 2 , as depicted in Figure 3, in order to study the effect of the linker in isoreticular COFs in the overall HER photocatalytic activity [32]. Another crystalline β-ketoenamine linked COF (TP-BDDA COF) has been synthesized by Thomas et al, in this case bearing diphenyl diacetylene bridges, by mixing TP and 4,4 -(buta-1,3-diyne-1,4-diyl)dianiline (BDDA) (Figure 3) [23].…”
Section: Common Synthetic Pathways To Build Efficient and Robust Cofsmentioning
confidence: 99%